Tissue ingrowth into perforated polymethylmethacrylate orbital implants: An experimental study - Miyashita, Denise; Chahud, Fernando; Da Silva, Gyl Eanes Barros; De Albuquerque, Verônica Batista; Garcia, Denny Marcos; Velasco E Cruz, Antonio Augusto (Wolters Kluwer, 2013)
Purpose: To evaluate the clinical response and fibrovascular ingrowth into perforated acrylic orbital implants in a rabbit model. Methods: Perforated implants were manufactured by drilling channels interconnected at the center in conventional 12- to 13-mm acrylic spheres. The implants were placed in 16 eviscerated eyes with posterior sclerotomy of 16 New Zealand white rabbits. Clinical evaluation was performed daily for the first 14 days after surgery and at 7-day intervals until the end of the study (180 days). Histopathologic analysis was performed at 14, 45, 90, and 180 days after implantation. Hematoxylin-eosin and picrosirius red staining was used to assess the inflammatory reaction and collagen formation. Results: There were no signs of infection, implant exposure, or extrusion in any animal during the study. Tissue ingrowth in the implant center was already detected by 14 days. At the end of the study, there was a dense collagen ingrowth with just a few inflammatory cells inside the implant. No multinucleated giant cells were found in any implant. Conclusions: Similar to porous implants, perforated acrylic implants permit fibrovascular ingrowth from surrounding orbital tissues. © 2013 The American Society of Ophthalmic Plastic and Reconstructive Surgery, Inc.